A Case of Reactive Eccrine Syringofibroadenoma Associated with Dyshidrotic Eczema - Chen Y; Tian X (Dove Medical Press, 2023)
Yue Chen, Xin Tian Guangzhou Institute of Dermatology, Guangzhou, Guangdong, People's Republic of ChinaCorrespondence: Xin Tian, Dermatology, Associate Director of Department of Dermatology, Guangzhou Institute of Dermatology, Guangzhou, Guangdong, People's Republic of China, Tel/Fax +86-20-83593472, Email xinzisue@163.comAbstract: Eccrine Syringofibroadenoma (ESFA) is an infrequent benign adnexal cutaneous lesion distinguished by hyperplastic epithelium and differentiation into eccrine ducts, displaying diverse clinical presentations. In the present case, a 48-year-old Chinese female patient exhibited a decade-long history of palmoplantar erythema, which clinically resembled Dyshidrotic Eczema. Histological examination suggested the presence of ESFA. Ultimately, considering both the clinical manifestations and histological outcomes, the patients received a diagnosis of reactive ESFA.Keywords: reactive eccrine syringofibroadenoma, dyshidrotic eczema, histopathology